Module for elementary school head teachers and principals on the evaluation of elementary science instruction - Granada, Judith Gayanelo (1976)
The purpose of the study was to meet the needs of head teachers and elementary principals in the administration and supervision of the elementary science program. An inter-unit modularity was adopted in this module on "Evaluation of Elementary Science Instruction," in which each unit was potentially developed in sequence. The module is self-contained and can bring about learning with a minimum of instructor supervision, especially so, when used as individualized learning package for principals and head teachers, particularly those assigned in remote areas.
Thesis (M.A. Elementary Science)--University of the Philippines, Diliman.
Keywords: Science -- Study and teaching (Elementary) -- Philippines -- Camarines Sur; Elementary school teachers -- Rating of -- Philippines -- Camarines sur; School principals -- In-service training -- Philippines -- Camarines Sur; Teaching -- Philippines -- Camarines Sur -- Aids and devices; Curriculum evaluation -- Philippines -- Camarines Sur